Examining the implementation of customer care as a strategy of enhancing service : a case study of Thulamela Local Municipality, Limpopo, South Africa - Munyai, Thinavhuyo Esther (My University, 2017)
The purpose of the research was to examine if the implementation of customer care has any effect on service delivery at Thulamela Local Municipality. Specifically the study focused on four main aspects, namely:to determine the effects of implementing customer care to enhance service delivery at Thulamela Local Municipality; to analyse the effects of enhancing customer care through quality service delivery; to investigate mechanisms of improving customer care through public relations; to explore the effect of implementing Batho-Pele principles in promoting customer care. The study used qualitative interviews to collect data from respondents. The study revealed that there was a relationship between customer care and service delivery and where customer care prevailed service delivery improved. The findings also strongly indicated that through public relations and the implementation of Batho-Pele principles, customer care can be enhanced and consequently quality service delivery. The study recommended that tools and systems should be developed that would motivate municipal employees to implement customer care. Training of municipal employees with regard to customer care was also emphasized. It was further recommended that the leadership at Thulamela Local Municipality should be morally sound for subordinates to follow.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Customer Care implementation; Thulamela Local Municipality; Customer relations; Customer services